Diagnostic value of additional 68Ga-PSMA-PET before 223Ra-dichloride therapy in patients with metastatic prostate carcinoma - Bräuer, Axel; Rahbar, Kambiz; Konnert, Julia; Bögemann, Martin; Stegger, Lars (Nuklearmedizin - NuclearMedicine, 2017)
Purpose: Medical imaging plays an important role in selecting patients with metastatic castration-resistant prostate cancer for 223Ra- dichloride therapy of bone metastases. The purpose of this study was to investigate whether 68Ga-PSMA-PET has incremental value over conventional imaging for selecting patients suitable for 223Ra-dichloride therapy. Methods: In 27 consecutive patients referred for 223Ra-dichloride therapy additional 68Ga-PSMA-PET/CT was performed and tracer distribution was evaluated systematically with respect to the detection of visceral metastases and bone metastases with inadequate uptake on bone scintigraphy. Results: In 4 patients (15 %) 68Ga- PSMA-PET revealed previously unknown visceral metastases (3 liver, 1 adrenal gland), which changed the therapeutic decision in 2 cases. PET revealed more extended tumour involvement in the bone compared to bone scintigraphy in 9 patients (33 %). In 3 of these, the mismatch was extensive enough to question suitability for 223Ra-dichloride therapy. Conclusions: Additional 68Ga-PSMA-PET as a gatekeeper between conventional staging and 223Ra-dichloride therapy can provide valuable additional information with regard to visceral metastases and tumour manifestations without adequate bone mineral turnover. It may lead to a change in therapeutic management in a significant number of patients and should therefore be considered in future clinical trials.
Keywords: prostate cancer; bone metastases; bone scintigraphy; 68Ga-PSMA-PET; 223Ra-dichloride; Xofigo®